PENERAPAN PROBLEM BASED LEARNING PADA MATERI OPERASI HITUNG PECAHAN KELAS VII SMP - Nur Hidayah; Agung Hartoyo; Dede Suratman (Universitas Tanjungpura, 2019)
AbstractThis research aimed to know the effectiveness of the implementation of problem based learning approach in fraction operations topic at class VII SMP Negeri 2 Pontianak. The research method used is pre-experimental method with the one-shot case study design. The aspect used to determine the effectiveness of the problem based learning approach are teacher’s class management, student’s activity and student’s outcomes. The Data collection tools used are test student’s outcomes which contains 4 essay and the observation sheet for teacher’s class management and student’s activity. The result of the descriptive analysis carried out are teacher’s class management categorized good (3,21), student’s activity categorized active enough (60%) and student’s completeness not fulfilled classically (only 23 students or 66% of students can fulfill the standard completeness). Because there was one aspect that not fulfilled, so the implementation of problem based learning approach in fraction operations topic at class VII SMP Negeri 12 Pontianak was not effective.Keywords : Application,Fraction operation,Problem Based Learning model